TRANSFORMASI HUKUM TATA NEGARA PASCA PUTUSAN MAHKAMAH KONSTITUSI TENTANG PENGHAPUSAN PRESIDENTIAL THRESHOLD DI INDONESIA: Constitutional Law Transformation After the Constitutional Court's Decision on the Elimination of the Presidential Threshold in Indonesia - Muhamad Iqbal Ansori Firdaus; Alfian Sugara; Harry Nurfandi; Muhamad Sahal Mubarok (Res Nullius Law Journal, 2026)
This research examines the transformation of constitutional law following the Constitutional Court's ruling on the elimination of the presidential threshold in Indonesian presidential elections. This ruling represents a fundamental shift in constitutional design, particularly regarding the presidential nomination mechanism and the dynamics of the party system. The research employs a normative juridical method, drawing on legislation, court decisions, and legal doctrine. The analysis focuses on the reconstruction of presidential nomination norms, their implications for strengthening the principle of popular sovereignty, and the consequences for the configuration of government in a multiparty system. The results indicate that the elimination of the presidential nomination threshold broadens the space for political participation, improves the quality of electoral democracy, and reinforces the people's position as holders of supreme sovereignty. However, this situation also creates the potential for political fragmentation and challenges in maintaining government effectiveness. The transformation of constitutional law stemming from this ruling emphasizes the need for the formulation of further regulations capable of maintaining a balance between political openness and government stability.